Italians in Valencia: A New Lifestyle Migration in an Urban Context - Ingellis, Anna Giulia; Stornaiuolo, Lavinia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
Over the last two decades, scholars have paid close attention to South-North intra-EU migration. In contrast, intra-Southern Europe migrations have not received the appropriate interest. This qualitative study, conducted between 2017 and 2019, investigates an emerging, fast-growing phenomenon: Italian migration to Spain, focusing on the Italian community in Valencia. Participant observation (virtual and traditional) and in-depth interviews (42) were used to study this migration process. Exploring the motivations to migrate, the subjective representation of the search for a better life, the meaning of lifestyle and the role of work in the migration process, the research explores how far it could be interpreted as a new lifestyle migration (LM) flow. The analysis reveals a complex combination of interrelated factors — like the Mediterranean lifestyle, good public services, low taxes, and cost of living — depicting the urban context of Valencia as a representative setting for a better quality of life.
Keywords: migratory motivations; Southern Europe; quality of life; facilities; Mediterranean lifestyle